Quaternary ammonium salt / magnetic biochar composite material, preparation method and application
By using alkaline chemical co-precipitation method in wastewater treatment, the quaternary ammonium salt/magnetic biochar composite materials are solved, and long-term sterilization and environmental protection savings are achieved The effect of the composite material is realized through the regeneration process.
Patent Information
- Application Number
- CN202411601561.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing sewage treatment technology cannot effectively remove pathogenic microorganisms and quaternary ammonium salt compounds in sewage wastewater, resulting in water quality safety threats and environmental pollution. The existing composite materials have problems such as high cost, difficulty in recycling and limited sterilization effects.
The magnetic iron-based biochar was prepared by alkaline chemical co-precipitation method, and combined with quaternary ammonium salt compounds through ion exchange method to form a quaternary ammonium salt/magnetic biochar composite material, achieving its sustained release performance and long-term bactericidal effect. The recycling and reuse of composite materials is achieved through the regeneration process.
It has achieved efficient removal of microorganisms in wastewater, reduced the release rate of quaternary ammonium salts and the risk of environmental pollution, and reduced production costs, which meets the requirements of green and sustainable development.
Smart Images

Figure CN119306301A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sewage and wastewater treatment, and specifically relates to a quaternary ammonium salt / magnetic biochar composite material, a preparation method and an application thereof. Background Art
[0002] With the rapid development of social economy, water shortage has seriously affected human activities and restricted social development. The recycling and reuse of sewage and wastewater is an effective way to alleviate water shortage and reduce the current water pollution situation. However, there are many problems in the actual reuse of recycled water. Studies have shown that a variety of pathogenic microorganisms will still remain in the initial water after conventional sewage treatment, such as Shigella, Salmonella, Campylobacter, Escherichia coli, enterovirus, etc., which may lead to the outbreak of diseases such as acute gastroenteritis and typhoid fever, seriously threatening human health and water environment safety. Efficient sterilization of recycled water is very necessary to ensure water quality safety.
[0003] Quaternary ammonium compounds (QACs) are a class of cationic surfactants and antimicrobial agents with broad-spectrum bactericidal effects, which are widely used in industries such as food processing and sewage treatment. As water-soluble chemical bactericides, quaternary ammonium salts have the disadvantages of difficult control of release rate, short antimicrobial activity cycle, easy bacteria to develop drug resistance, and residual toxicity of disinfectants themselves polluting the environment when used alone. Conventional sewage treatment technology cannot remove quaternary ammonium salts. A large amount of quaternary ammonium compounds are absorbed by activated sludge or discharged into the environment with effluent, causing serious pollution of surface water, rivers, etc., which seriously restricts the use of quaternary ammonium compounds as antimicrobial agents. After quaternary ammonium compounds are fixed on the surface of porous materials through chemical bonds to make quaternary ammonium modified materials, not only can the rapid diffusion and biocidal effects of quaternary ammonium salts be overcome, but also the materials can maintain long-term antimicrobial activity, effectively realizing the high efficiency, low toxicity and slow release performance of antimicrobial agents.
[0004] Common carriers of existing antibacterial agents mainly include clay minerals, diatomaceous earth, metal organic framework materials, graphene oxide, inorganic microporous materials, etc. Studies have found that when graphene oxide is used as a carrier of bactericidal materials, the bactericidal effect is better, but the production cost is expensive and it is difficult to produce on a large scale and apply in actual production. Composite materials made from carriers with a wide range of material sources and low costs, such as PTQ (chlorinated natural rubber-quaternary ammonium salt), HNTs-CS@Ag (chitosan nanosilver composite materials), etc., have general bactericidal effects and large dosages. In addition, composite bactericidal materials supported by cheaper carriers such as diatomaceous earth and clay minerals reduce the economic cost of production, but the use of such composite materials will increase the possibility of clogging of pipelines, equipment, etc., and such materials are difficult to recycle and reuse. CN105284812A discloses a broad-spectrum antibacterial amphiphilic biocarbon material and its preparation method and use. The broad-spectrum antibacterial agent quaternary ammonium salt is uniformly fixed on the surface of the amphiphilic biocarbon material by a covalent coupling method and a distillation precipitation polymerization method. The obtained broad-spectrum antibacterial amphiphilic biocarbon material has the advantages of broad-spectrum antibacterial property, antibacterial lasting stability and reusability, but the preparation method is complicated and does not have the characteristics of being recyclable and reusable. CN107398256A discloses a magnetic straw quaternary ammonium salt / rectorite composite material and its preparation method and application. The magnetic straw quaternary ammonium salt / rectorite composite material is prepared by a liquid phase method using rice straw, rectorite and 3-chloro-2-hydroxypropyltrimethylammonium chloride as raw materials, solving the problem that water treated with straw quaternary ammonium salt flocculant often contains flocs, but there may be a problem that rectorite, as natural clay, increases the burden on pipelines, and the sterilization effect and recovery effect are limited.
[0005] Therefore, there are few reports on bactericidal materials that can simultaneously remove pathogens in recycled water during the wastewater reuse process. In addition, due to the defects of existing composite materials and the inadequacies of preparation technology, there is an urgent need to develop a new type of composite material with low cost, long-term bactericidal effect and repeatable recycling and reuse, which is of great significance for the safe reuse of sewage and wastewater. Summary of the invention
[0006] In view of the above problems, the present invention provides a quaternary ammonium salt / magnetic biochar composite material, a preparation method and an application thereof, wherein rice husk-based biochar is prepared using agricultural waste rice husk as a raw material, magnetic iron-based biochar is synthesized by an alkaline chemical coprecipitation method, and then the quaternary ammonium salt / magnetic biochar composite material is prepared by an ion exchange method with a quaternary ammonium salt compound, and the obtained composite material has excellent slow-release quaternary ammonium salt performance and a long-lasting and significant bactericidal effect. Secondly, a regenerated quaternary ammonium salt / magnetic biochar composite material can be prepared using the used quaternary ammonium salt / magnetic biochar composite material as a raw material, and the composite material can be recycled and reused, and the bactericidal effect is better than that of the composite material prepared for the first time. The biochar composite material can be applied to sewage treatment, and lays a foundation for the efficient removal of microorganisms in sewage.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] On the one hand, the present invention provides a method for preparing a quaternary ammonium salt / magnetic biochar composite material, which is characterized in that rice husk-based biochar is used as a carrier and an alkaline chemical co-precipitation method is used to synthesize magnetic iron-based biochar, and then the quaternary ammonium salt / magnetic biochar composite material is prepared by an ion exchange method with a quaternary ammonium salt compound.
[0009] The above preparation method comprises the following steps:
[0010] (1) Preparation of rice husk-based biochar:
[0011] ① The carbonized product is obtained by washing and drying the rice husk to a constant weight and then carbonizing it at high temperature;
[0012] ② Wash, dry, grind and sieve the carbonized product obtained in step ① to obtain rice husk-based biochar;
[0013] (2) Preparation of magnetic iron-based biochar:
[0014] ① Place the rice husk-based biochar obtained in step (1) in deionized water and subject it to ultrasonic vibration to obtain a biochar suspension;
[0015] ②Place FeSO 4 7H 2 O and FeCl 3 6H 2 O is dissolved in dilute hydrochloric acid solution in N 2 Stirring under ambient conditions, adjusting pH with aqueous ammonia to obtain a magnetic iron-based solution;
[0016] ③ Add the biochar suspension prepared in step ① to the magnetic iron-based solution obtained in step ② under water bath conditions while stirring, cool to room temperature, separate the product with a permanent magnet, and obtain the magnetic iron-based biochar after washing, drying and sieving the magnetic product;
[0017] (3) Preparation of quaternary ammonium salt / magnetic biochar composite material: After adding the magnetic iron-based biochar obtained in step (2) into deionized water, add quaternary ammonium salt compounds to fully impregnate, carry out hydrothermal reaction and then cool, separate the product with a permanent magnet, and then wash, vacuum dry, grind and sieve to obtain a quaternary ammonium salt / magnetic biochar composite material.
[0018] Furthermore, the rice husks in step (1) are washed 2-3 times; the drying temperature is 60-70°C for 10-15 hours; the high-temperature carbonization method is: placing the rice husks in a tubular furnace and passing N at a constant rate of 3-5 L / h. 2 , heat up to 500-600℃ at a rate of 10-20℃ / min, and stop N after carbonization for 1-3h.2 Aeration, aeration with a concentration of 15-20% CO 2 The reaction was carried out for 1-2 h under N 2 Cool to room temperature in a protective atmosphere.
[0019] Furthermore, the carbonized product in step (1) is washed 3-5 times until the pH value of the washing solution is neutral; the drying temperature is 60-70°C and the time is 20-30h; the filter sieve aperture range is 90-110 mesh; and the particle size of the rice husk-based biochar is 0.9-1.2mm.
[0020] Furthermore, in step (2), the weight ratio of the rice husk-based biochar to deionized water is 1:8-12; the frequency of the ultrasonic oscillation is 20-80 kHz, and the time is 3-5 h.
[0021] Furthermore, in step (2), the FeSO 4 7H 2 O, FeCl 3 6H 2 O and dilute hydrochloric acid solution is 1:2-4:10-15, the concentration of dilute hydrochloric acid is 0.3-0.5 mol / L; the concentration of ammonia water is 20-30%, and the pH value of the magnetic iron-based solution is 9.5-10.5.
[0022] Furthermore, in step (2), the volume ratio of the magnetic iron-based solution to the biochar suspension is 1:3-5; the water bath temperature is 65-75°C, and the stirring time is 1.5-3h; the washing method is: first washing with anhydrous ethanol, then washing with deionized water, the washing times are 1-3 times and 3-5 times respectively, until the pH value of the washing solution is neutral; the drying temperature is 65-80°C, and the time is 24-48h; the filter sieve aperture range is 90-110 mesh.
[0023] Furthermore, the quaternary ammonium salt compound in step (3) is one or two of tetradecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium chloride.
[0024] Furthermore, in step (3), the weight ratio of the magnetic iron-based biochar, the quaternary ammonium salt compound, and the deionized water is 1:10-50:100-400, the amount of deionized water added is sufficient for full immersion, and the immersion time is 12-20 hours.
[0025] Furthermore, in step (3), the hydrothermal reaction temperature is 60-70°C and the time is 3-5h; the washing times are 3-5 times until the pH value of the washing solution is neutral; the vacuum drying temperature is 65-75°C and the time is 24-48h; and the filter sieve aperture range is 90-110 mesh.
[0026] On the other hand, the regenerated quaternary ammonium salt / magnetic biochar composite material can be prepared using the used quaternary ammonium salt / magnetic biochar composite material as a raw material.
[0027] A method for preparing a regenerated quaternary ammonium salt / magnetic biochar composite material is characterized in that the used quaternary ammonium salt / magnetic biochar composite material is washed, dried and sieved, and then subjected to an ion exchange method with a quaternary ammonium salt compound to prepare the regenerated quaternary ammonium salt / magnetic biochar composite material.
[0028] The above preparation method comprises the following steps:
[0029] (1) Separating and recovering the used quaternary ammonium salt / magnetic biochar composite material with a permanent magnet, washing with deionized water for 3-5 times until the washing liquid is neutral; drying at 65-80° C. for 24-48 hours, and grinding through a 90-110 mesh sieve to obtain a recovered material;
[0030] (2) After adding the recovered material obtained in step (1) into deionized water, adding a quaternary ammonium salt compound to fully immerse it, performing a hydrothermal reaction and then cooling, separating the product with a permanent magnet, and then washing, vacuum drying, grinding and sieving to obtain a regenerated quaternary ammonium salt / magnetic biochar composite material.
[0031] Furthermore, the quaternary ammonium salt compound in step (2) is one or two of tetradecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium chloride.
[0032] Furthermore, in step (2), the weight ratio of the recycled material, the quaternary ammonium salt compound and the deionized water is 1:10-50:100-400, the amount of deionized water added is sufficient for full immersion, and the immersion time is 12-20 hours.
[0033] Furthermore, in step (2), the hydrothermal reaction temperature is 60-70°C and the time is 3-5 hours; the washing times are 3-5 times until the pH value of the washing solution is neutral; the vacuum drying temperature is 65-75°C and the time is 24-48 hours; and the filter sieve aperture range is 90-110 mesh.
[0034] The present invention also provides an application of a quaternary ammonium salt / magnetic biochar composite material or a regenerated quaternary ammonium salt / magnetic biochar composite material in sewage and wastewater treatment.
[0035] The specific method of the above application is: adding the quaternary ammonium salt / magnetic biochar composite material or the regenerated quaternary ammonium salt / magnetic biochar composite material into sewage and wastewater at a usage amount of 20-50 mg / L.
[0036] Beneficial effects:
[0037] (1) The quaternary ammonium salt / magnetic biochar composite material prepared by the present invention uses biochar as the original load material, and the raw materials for burning are agricultural wastes with a wide range of sources, thus realizing the resource utilization of solid wastes and biochar materials, which is conducive to further promotion and application.
[0038] (2) The quaternary ammonium salt / magnetic biochar composite material prepared by the present invention combines biochar with magnetic particles to prepare magnetic iron-based biochar. The composite material can be separated from water by a permanent magnet to achieve the reuse of the composite material. It has the advantages of environmental protection, low cost, etc., and is conducive to promotion and application.
[0039] (3) The quaternary ammonium salt / magnetic biochar composite material prepared by the present invention loads a bactericide quaternary ammonium salt compound on the surface of the magnetic biochar. The composite material has good bactericidal performance and sustained-release function, and can effectively solve the problems of difficult control of the release rate of the water-soluble bactericide quaternary ammonium salt when used alone, short antibacterial activity cycle, inability to be reused, and secondary pollution of water bodies caused by the residual disinfectant itself.
[0040] (4) In the process of loading quaternary ammonium salt, the magnetic iron-based biochar is fully impregnated with the quaternary ammonium salt compound and then subjected to hydrothermal reaction, which can activate and strengthen the combination of the quaternary ammonium salt and the magnetic biochar to the greatest extent, thereby increasing the loading amount of the quaternary ammonium salt on the surface of the magnetic biochar and effectively enhancing the bactericidal performance of the composite material; secondly, the quaternary ammonium salt is fixed on the surface of the magnetic biochar through chemical bonds to form a quaternary ammonium salt modified material, so that the composite material can maintain long-term antibacterial activity.
[0041] (5) The quaternary ammonium salt / magnetic biochar composite material obtained by the present invention is a quaternary ammonium salt polymer material, which can adsorb free bacteria and the like through the high-density charge on the surface of the material, thereby avoiding the generation of drug resistance and secondary environmental pollution to a certain extent.
[0042] (6) The quaternary ammonium salt / magnetic biochar composite material prepared by the present invention can be recycled, and the bactericidal effect of the recycled composite material is better than that of the composite material prepared for the first time, which meets the current green and sustainable industry development requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a scanning electron microscope image of magnetic iron-based biochar;
[0044] Figure 2 Schematic diagram of the quaternary ammonium salt / magnetic biochar composite material after loading the quaternary ammonium salt;
[0045] Figure 3 This is the sustained release curve of quaternary ammonium salt in quaternary ammonium salt / magnetic biochar composite material. DETAILED DESCRIPTION
[0046] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Example 1 Preparation of magnetic iron-based biochar
[0048] A method for preparing magnetic iron-based biochar, the specific steps are as follows:
[0049] (1) Preparation of rice husk-based biochar:
[0050] ① The rice husk was washed twice with deionized water, dried in a drying oven at 60°C for 12 h until constant weight was obtained, and then collected. The obtained rice husk was placed in a tube furnace and N was introduced at a constant rate of 4 L / h. 2 , the temperature was raised to 550℃ at a rate of 15℃ / min, and the N 2 Into, change to 20% CO 2 After 1.5 h of reaction, 2 Cooling to room temperature in a protective atmosphere to obtain a carbonized product;
[0051] ② Wash the carbonized product obtained in step ① 4 times until the pH value of the washing solution is neutral, dry it in a drying oven at 60° C. for 24 h, and grind the dried material through a 100-mesh sieve to obtain rice husk-based biochar with a particle size of 0.9-1.2 mm;
[0052] (2) Preparation of magnetic iron-based biochar
[0053] ① Mix rice husk-based biochar and deionized water in a weight ratio of 1:10, and ultrasonically vibrate at a frequency of 40 kHz for 4 hours to obtain a fully mixed and uniform biochar suspension;
[0054] ②Take 3.0g FeSO 4 7H 2 O and 8.5 g FeCl 3 6H 2 O was dissolved in 38 mL of 0.4 mol / L dilute hydrochloric acid solution. 2 Rapidly stir in an environment, and rapidly drop 25% ammonia water while stirring to adjust the pH value of the solution to 10 to obtain a magnetic iron-based solution;
[0055] ③ In a 70°C water bath, add 160 ml of the biochar suspension prepared in step ① to the magnetic iron-based solution obtained in step ② while stirring, stir for 2 hours and cool to room temperature; use a permanent magnet to separate the products, wash the obtained product twice with anhydrous ethanol and then four times with deionized water until the pH value of the washing solution is neutral, dry it at 70°C for 30 hours, grind it and pass it through a 100-mesh sieve to obtain magnetic iron-based biochar.
[0056] The magnetic iron-based biochar obtained above was observed using a scanning electron microscope to observe the loading of magnetic iron particles. Figure 1 As shown, a large amount of magnetic iron particles were loaded on the surface of rice husk biochar.
[0057] Example 2 Preparation of quaternary ammonium salt / magnetic biochar composite material
[0058] A method for preparing a quaternary ammonium salt / magnetic biochar composite material, the specific steps are as follows:
[0059] 1.0 g of the magnetic iron-based biochar prepared in Example 1 was added to 100 ml of deionized water, 10.0 g of tetradecyltrimethylammonium chloride was added, and the mixture was stirred continuously for 15 h at room temperature for full impregnation. The mixture was reacted in a water bath at 65 ° C for 4 h, cooled to room temperature, and the product was magnetically separated with a permanent magnet to obtain a magnetic separation product. The product was repeatedly washed with deionized water for 4 times until the pH value of the washing solution was neutral. The washed product was placed in a vacuum drying oven at 70 ° C and dried for 30 h. The product was ground through a 100-mesh sieve to obtain a quaternary ammonium salt / magnetic biochar composite material with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:10.
[0060] Thermogravimetric analysis showed that 5.71% of the quaternary ammonium salt compounds were loaded on the magnetic iron-based biochar in the quaternary ammonium salt / magnetic biochar composite material obtained by using a mass ratio of magnetic biochar to quaternary ammonium salt of 1:10. The schematic diagram of the loaded quaternary ammonium salt / magnetic biochar is shown in FIG. Figure 2 shown.
[0061] Example 3 Preparation of quaternary ammonium salt / magnetic biochar composite material
[0062] A method for preparing a quaternary ammonium salt / magnetic biochar composite material, the specific steps are as follows:
[0063] 1.0 g of the magnetic iron-based biochar prepared in Example 1 was added to 300 ml of deionized water, and 30.0 g of a quaternary ammonium salt compound was added. After continuous stirring for 15 h at room temperature for full impregnation, the mixture was reacted in a water bath at 65 ° C for 4 h, cooled to room temperature, and the product was magnetically separated with a permanent magnet to obtain a magnetic separation product; the product was repeatedly washed with deionized water for 4 times until the pH value of the washing solution was neutral, and the washed product was placed in a vacuum drying oven at 70 ° C for 30 h, and ground through a 100 mesh sieve to obtain a quaternary ammonium salt / magnetic biochar composite material with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:30.
[0064] Thermogravimetric analysis showed that 11.39% of the quaternary ammonium salt compounds were loaded on the magnetic iron-based biochar in the quaternary ammonium salt / magnetic biochar composite material obtained by using a magnetic biochar to quaternary ammonium salt mass ratio of 1:30.
[0065] Example 4 Preparation of quaternary ammonium salt / magnetic biochar composite material
[0066] A method for preparing a quaternary ammonium salt / magnetic biochar composite material, the specific steps are as follows:
[0067] 1.0 g of the magnetic iron-based biochar prepared in Example 1 was added to 400 ml of deionized water, and 50.0 g of a quaternary ammonium salt compound was added. After continuous stirring for 15 h at room temperature for full impregnation, the mixture was reacted in a water bath at 65 ° C for 4 h, cooled to room temperature, and the product was magnetically separated with a permanent magnet to obtain a magnetic separation product; the product was repeatedly washed with deionized water for 4 times until the pH value of the washing solution was neutral, and the washed product was placed in a vacuum drying oven at 70 ° C for 30 h, and ground through a 100 mesh sieve to obtain a quaternary ammonium salt / magnetic biochar composite material with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:50.
[0068] Thermogravimetric analysis showed that 19.25% of the quaternary ammonium salt compounds were loaded on the magnetic biochar in the quaternary ammonium salt / magnetic biochar composite material obtained with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:50.
[0069] Example 5 Determination of sustained release performance of quaternary ammonium salt / magnetic biochar composite material
[0070] The sustained release performance of the quaternary ammonium salt in the quaternary ammonium salt / magnetic biochar composite material obtained in Example 2-4 was measured. 10 mg of each quaternary ammonium salt / magnetic biochar composite material prepared in Example 2-4 was taken and added to 10 mL of ultrapure water respectively, and placed in a shaker at 170 rpm and continuously shaken at room temperature for 72 h. Samples were taken at 0, 6, 12, 18, 24, 30, 36, 42, 48, 54, 60, 66, and 72 h, respectively. After the samples were filtered through a 0.45 μm filter membrane, the content of quaternary ammonium salt dissolved in the filtrate of the quaternary ammonium salt / magnetic biochar composite material was detected by the disulfide blue method (referenced from Tezel, U., Pierson, JA, & Pavlostathis, SG (2006). Fate and effect of quaternary ammonium compounds on amixed methanogenic culture. Water Research, 40 (19), p. 3660-3668.).
[0071] like Figure 3 As shown, the test results show that with the extension of the immersion time, the release of quaternary ammonium salt in the composite bactericidal material gradually increases. After 72 hours of shaking culture, the total release of quaternary ammonium salt of the three composite materials is 47.6, 89.5 and 134.8 mg / L, respectively, which is only 4.76%, 8.95% and 13.48% of the initial addition amount, respectively. It can be seen that the quaternary ammonium salt / magnetic biochar composite material prepared by the present invention has excellent slow-release quaternary ammonium salt performance, can solve the problem of difficult control of quaternary ammonium salt release rate, and prolong the bactericidal action time.
[0072] Example 6 Determination of antibacterial effect of quaternary ammonium salt / magnetic biochar composite material
[0073] Escherichia coli and Staphylococcus aureus, two common pathogenic strains in two types of sewage and wastewater, were selected to represent Gram-negative bacteria and Gram-positive bacteria, respectively. The bactericidal effect of the quaternary ammonium salt / magnetic biochar composite material obtained in Example 2-4 at different dosages was determined with reference to GB / T14643.2-2009 "Detection Method for Bacteria and Algae in Industrial Circulating Cooling Water". The specific experimental settings and bactericidal effects are shown in Table 1.
[0074] As shown in Table 1, the quaternary ammonium salt / magnetic biochar composite material prepared by the present invention has good bactericidal properties against both Escherichia coli and Staphylococcus aureus. For the same type of quaternary ammonium salt / magnetic biochar composite material, the bactericidal effect gradually increases with the increase in the dosage; secondly, the bactericidal effect against Escherichia coli and Staphylococcus aureus increases with the increase in the quaternary ammonium salt loading rate in the quaternary ammonium salt / magnetic biochar composite material. This indicates that the quaternary ammonium salt / magnetic biochar composite material prepared by the present invention has good bactericidal properties against both Gram-positive bacteria and Gram-negative bacteria.
[0075] Table 1 Comparison of bactericidal effects of composite materials with different loading ratios at different dosages
[0076]
[0077] Example 7 Comparative determination of the bactericidal effect of quaternary ammonium salt / magnetic biochar composite materials and existing bactericidal materials
[0078] GO-1227 material is an organic bactericidal material provided by Nanjing Institute of Soil Science, Chinese Academy of Sciences;
[0079] PS / Ag material is a disinfection material with a simple preparation method, provided by the School of Environment, Harbin Institute of Technology;
[0080] PTQ material is a bactericidal material synthesized from natural rubber and provided by the School of Environment of Harbin Institute of Technology.
[0081] The common pathogenic strains of Escherichia coli and Staphylococcus aureus in sewage and wastewater were selected, and the bactericidal effects of the quaternary ammonium salt / magnetic biochar composite material with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:10 prepared in Example 2, GO-1227, PS / Ag and PTQ were determined with reference to GB / T14643.2-2009 "Detection Method of Bacteria and Algae in Industrial Circulating Cooling Water", and the dosage of each existing bactericidal material was the optimal dosage. The specific experimental settings and bactericidal effects are shown in Table 2.
[0082] As shown in Table 2, GO-1227 material, as an organic bactericidal material, has a low dosage, but the cost is high, and the operating cost is high in the actual application process; PS / Ag, as a disinfectant material with a simple preparation method, has a general bactericidal effect and a large actual usage amount; PTQ, as a bactericidal material synthesized from natural rubber, has a wide range of preparation materials and low synthesis production costs, but has a general bactericidal effect and a large dosage in actual application. As can be seen from the comparison results, the quaternary ammonium salt / magnetic biochar composite material prepared by the present invention can obtain a better bactericidal effect at a lower dosage, which is more practical than existing bactericidal materials.
[0083] Table 2 Comparison of bactericidal effects between quaternary ammonium salt / magnetic biochar composite materials and existing bactericidal materials
[0084]
[0085] Example 8 Preparation of regenerated quaternary ammonium salt / magnetic biochar composite material
[0086] A method for preparing a regenerated quaternary ammonium salt / magnetic biochar composite material, the specific steps are as follows:
[0087] (1) The used quaternary ammonium salt / magnetic biochar composite material was magnetically separated and recovered using a permanent magnet, and washed with deionized water for 4 times until the washing liquid was neutral; dried at 70° C. for 30 h, and ground through a 100-mesh sieve to obtain a recycled material;
[0088] (2) According to the preparation method of Example 2-4, the "1.0 g of magnetic iron-based biochar prepared in Example 1" in Example 2-4 was replaced by "1.0 g of recycled material obtained in step (1)", and the other steps were the same, and regenerated quaternary ammonium salt / magnetic biochar composite materials with a mass ratio of magnetic biochar to quaternary ammonium salt of 1:30, 1:40, and 1:50 were prepared respectively.
[0089] Example 9 Determination of antibacterial effect of regenerated quaternary ammonium salt / magnetic biochar composite material
[0090] Escherichia coli and Staphylococcus aureus, two common pathogenic strains in two types of sewage and wastewater, were selected to represent Gram-negative bacteria and Gram-positive bacteria, respectively. The bactericidal effects of different types of regenerated quaternary ammonium salt / magnetic biochar composites prepared in Example 8 at different dosages were determined with reference to GB / T14643.2-2009 "Detection Method for Bacteria and Algae in Industrial Circulating Cooling Water". The specific experimental settings and bactericidal effects are shown in Table 3.
[0091] Table 3 Comparison of bactericidal effects of quaternary ammonium salt / magnetic biochar composites and regenerated quaternary ammonium salt / magnetic biochar composites
[0092]
[0093] As shown in Table 3, the bactericidal effect of the regenerated quaternary ammonium salt / magnetic biochar composite material is higher than that of the quaternary ammonium salt / magnetic biochar composite material prepared for the first time, because the quaternary ammonium salt group is still retained on the recycled material, and the loading amount of the quaternary ammonium salt on the surface of the magnetic biochar is increased during the secondary preparation process, thereby improving the bactericidal effect. The quaternary ammonium salt / magnetic biochar composite material preparation method of the present invention can not only realize the recycling of the composite material, but also the bactericidal effect of the regenerated quaternary ammonium salt / magnetic biochar composite material prepared with the recycled material as raw material is better, giving full play to the advantages and characteristics of the material itself, and providing a new material and a new method for solving the pollution problem of pathogens in water bodies.
Claims
1. A method for preparing a quaternary ammonium salt / magnetic biochar composite material, characterized in that: Magnetic iron-based biochar was synthesized using alkaline chemical co-precipitation method with rice husk-based biochar as carrier, and then it was prepared into quaternary ammonium salt / magnetic biochar composite material by ion exchange method with quaternary ammonium salt compounds.
2. The method for preparing the quaternary ammonium salt / magnetic biochar composite material according to claim 1, characterized in that: The method comprises the following steps: (1) Preparation of rice husk-based biochar: ① The carbonized product is obtained by washing and drying the rice husk to a constant weight and then carbonizing it at high temperature; ② Wash, dry, grind and sieve the carbonized product obtained in step ① to obtain rice husk-based biochar; (2) Preparation of magnetic iron-based biochar: ① Place the rice husk-based biochar obtained in step (1) in deionized water and subject it to ultrasonic vibration to obtain a biochar suspension; ② Dissolve FeSO4·7H2O and FeCl3·6H2O in dilute hydrochloric acid solution and stir under N2 environment, adjust pH with ammonia water to obtain magnetic iron-based solution; ③ Add the biochar suspension prepared in step ① to the magnetic iron-based solution obtained in step ② under water bath conditions while stirring, cool to room temperature, separate the product with a permanent magnet, and obtain the magnetic iron-based biochar after washing, drying and sieving the magnetic product; (3) Preparation of quaternary ammonium salt / magnetic biochar composite material: After adding the magnetic iron-based biochar obtained in step (2) into deionized water, add quaternary ammonium salt compounds to fully impregnate, carry out hydrothermal reaction and then cool, separate the product with a permanent magnet, and then wash, vacuum dry, grind and sieve to obtain a quaternary ammonium salt / magnetic biochar composite material.
3. The preparation method according to claim 2, characterized in that: The rice husks in step (1) are washed 2-3 times; the drying temperature is 60-70° C. and the drying time is 10-15 hours; The high-temperature carbonization method comprises placing the rice husk in a tube furnace, introducing N2 at a constant rate of 3-5 L / h, heating to 500-600° C. at a rate of 10-20° C. / min, stopping the introduction of N2 after carbonization for 1-3 hours, introducing CO2 with a concentration of 15-20% for reaction for 1-2 hours, and cooling to room temperature in a N2 protective atmosphere; The carbonized product is washed 3-5 times until the pH value of the washing liquid is neutral; the drying temperature is 60-70° C. and the time is 20-30 hours; the filter sieve aperture range is 90-110 mesh; and the particle size of the rice husk-based biochar is 0.9-1.2 mm.
4. The preparation method according to claim 2, characterized in that: In step (2), the weight ratio of the rice husk-based biochar to deionized water is 1:8-12; the frequency of the ultrasonic oscillation is 20-80 kHz, and the time is 3-5 hours; The weight ratio of the FeSO4·7H2O, FeCl3·6H2O and dilute hydrochloric acid solution is 1:2-4:10-15, the concentration of dilute hydrochloric acid is 0.3-0.5 mol / L; the concentration of the ammonia water is 20-30%, and the pH of the magnetic iron-based solution is 9.5-10.5; The volume ratio of the magnetic iron-based solution to the biochar suspension is 1:3-5; the water bath temperature is 65-75°C, and the stirring time is 1.5-3h; the washing method is: first washing with anhydrous ethanol, then washing with deionized water, the washing times are 1-3 times and 3-5 times respectively, until the pH value of the washing solution is neutral; the drying temperature is 65-80°C, and the time is 24-48h; the pore size range of the filter screen is 90-110 mesh.
5. The preparation method according to claim 2, characterized in that: The quaternary ammonium salt compound in step (3) is one or two of tetradecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium chloride; The weight ratio of the magnetic iron-based biochar, quaternary ammonium salt compound and deionized water is 1:10-50:100-400, and the immersion time is 12-20 hours; the hydrothermal reaction temperature is 60-70°C, and the time is 3-5 hours; the washing times is 3-5 times, until the pH value of the washing liquid is neutral; the vacuum drying temperature is 65-75°C, and the time is 24-48 hours; the filter sieve aperture range is 90-110 mesh.
6. A quaternary ammonium salt / magnetic biochar composite material prepared according to the preparation method according to any one of claims 1 to 5.
7. A method for preparing a regenerated quaternary ammonium salt / magnetic biochar composite material, characterized in that: The used quaternary ammonium salt / magnetic biochar composite material according to claim 1 is washed, dried, ground and sieved, and then subjected to ion exchange with a quaternary ammonium salt compound to prepare a regenerated quaternary ammonium salt / magnetic biochar composite material.
8. The regenerated quaternary ammonium salt / magnetic biochar composite material prepared by the preparation method according to claim 7.
9. Use of the quaternary ammonium salt / magnetic biochar composite material according to claim 6 in sewage and wastewater treatment.
10. Use of the regenerated quaternary ammonium salt / magnetic biochar composite material according to claim 8 in sewage and wastewater treatment.
Citation Information
Patent Citations
Broad-spectrum antibacterial amphiphilic biological carbon material, and preparation method and application thereof
CN105284812A
Magnetic straw quaternary ammonium salt / rectorite composite material and preparation method thereof
CN107398256A
Magnetic rice straw adsorbent as well as preparation method and application thereof
CN107469780A
Magnetic biomass carbon-quaternary phosphonium salt sterilization material, and preparation method and using method thereof
CN110226604A
Polymorphic phosphorus adsorbent and preparation method thereof
CN118767871A